Delaying early morning workouts to protect sleep in two-a-day athletes - Youngstedt, Shawn D. (Frontiers in Physiology, 2024)
Two-a-day training is common for endurance athletes with training sessions typically beginning at 6 am and 3 pm or 4 pm. However, the early morning workouts could contribute to significant sleep loss, especially for night owls. Chronic sleep loss over a season could result in impaired performance, as well as an increased risk of physical and mental illness. It is hypothesized that shifting the early morning workout to later in the day could have beneficial effects for these athletes. A number of obstacles could make this hypothesis difficulty to test and implement.However, such a change could have dramatic benefits for some athletes.